Agricultural price policy for developing countries - Mellor, John W.; Ahmed, Raisuddin (International Food Policy Research Institute, 1988)
The weight of agricultural prices in political debate, their searing importance to the poor, and their common association with unusually low agricultural output levels often lead to policies that focus directly on prices at the expense of other underlying economic relations. In contrast, our objective is to focus explicitly on agricultural price policy in the context of economic growth and, more specifically, of technological change. In the recent past, and in some cases even now, developing countries have followed foreign trade, exchange rate, and domestic policies which have so grossly distorted agricultural prices as to call for a singleminded focus on removing those gross distortions. We note such circumstances and their causes but look beyond "once-and-for-all" price adjustments to the process of technological change and the institutional changes that go, paripassu, with technological change. Agricultural price policy is important to those processes, and it is that interaction to which we constantly return.